The Role of The Community in Inclusive Education - Istigfarin, Agnia; Sukmana, Nishrina Gyna Hafiza; Mastiani, Emay (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The current inclusive education has not been fully realized. The community also does not fully understand the paradigm of inclusive education and therefore cannot contribute much to it. The role of the community is a very important component for the success of inclusive education, because the community has various resources needed by the school and at the same time the community is also the owner of the school in addition to the government. When community participation can be maximized in supporting inclusive education, the goal of education for welfare will be achieved. The purpose of this study is to find out how the role of the community in the sustainability of inclusive education.